Efficacy of vitamin C and ethanolic extract of Sesamum indicum in promoting fertility in male Wistar rats - E A Ashamu; E O Salawu; O O Oyewo; A W Alhassan; O A Alamu; A A Adegoke (Wolters Kluwer Medknow Publications, 2010)
Aims: This study investigates the efficacy of ethanolic extract of Sesamum indicum (EES), vitamin C (VC), and EES + VC in promoting fertility and finding a possible link between their profertility effects and their antioxidant activities. Materials and Methods: Forty adult male Wistar rats [Body weight (BW) 186.56 ± 0.465 g] were randomly analyzed into four groups of ten rats each: Control, EES G (EES only), VC G (vitamin C only), and EES + VC G (EES in conjunction with vitamin C). Control was given 5 ml/kg BW/day of normal saline orally; EES G was administered 0.3 g/kg BW/day of EES; VC G was administered 15 mg/kg BW/ day of VC; while EES + VC G was administered both 0.3 g/kg BW/day of EES and 15 mg/kg BW/day of VC. All treatments were for 10 weeks. Statistical Analysis Used: Independent-sample T test was used to analyze the obtained results. Results: The results obtained showed that EES, VC, and more importantly EES + VC are capable of significantly increasing BW gain, seminal parameters, testosterone level, and body antioxidant activities. Conclusions: These findings lead to the conclusion that EES + VC as well as ESS and VC promote fertility due to both their testosterone-increasing effects and their antioxidant effects.